2008
DOI: 10.1016/j.tcs.2008.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Generalized LCS

Abstract: a b s t r a c tThe Longest Common Subsequence (LCS) is a well studied problem, having a wide range of implementations. Its motivation is in comparing strings. It has long been of interest to devise a similar measure for comparing higher dimensional objects, and more complex structures. In this paper we study the Longest Common Substructure of two matrices and show that this problem is N P -hard. We also study the Longest Common Subforest problem for multiple trees including a constrained version, as well. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
(32 reference statements)
0
23
0
Order By: Relevance
“…Our set of problems are very different from the traditional LCS problems for higher dimensional structures [15,1]. All of them are duals of the edit distance problem and our problems aren't.…”
Section: Taxonomy Of Problemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our set of problems are very different from the traditional LCS problems for higher dimensional structures [15,1]. All of them are duals of the edit distance problem and our problems aren't.…”
Section: Taxonomy Of Problemsmentioning
confidence: 99%
“…We continue the same process again. However, we found that this LCS(T (i), C(j)) = ( T (i) = C(j) LCS(lef t(T (i)), C(j + 1)) + LCS(right(T (i)), C(j + 1)) + 1 T (i) = C(j) max(LCS(T (i), C(j + 1)), (LCS(lef t(T (i)), C(j)) + LCS(right(T (i)), C(j)))) (1) approach was also not sufficient. At some point, we unmerge all the vertices and start from scratch.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, it inserts context and/or hedge variables into the skeleton, which are supposed to uniformly generalize (vertical and horizontal) differences between input hedges, to obtain an lgg (with respect to the given skeleton). The skeleton computation function is the parameter of the algorithm: One can compute an lgg which contains, for instance, a constrained longest common subforest [1], or an agreement subhedge/subtree [5] of the input hedges.…”
Section: Introductionmentioning
confidence: 99%